2008
DOI: 10.1038/nature06840
|View full text |Cite
|
Sign up to set email alerts
|

The earliest thymic progenitors for T cells possess myeloid lineage potential

Abstract: There exists controversy over the nature of haematopoietic progenitors of T cells. Most T cells develop in the thymus, but the lineage potential of thymus-colonizing progenitors is unknown. One approach to resolving this question is to determine the lineage potentials of the earliest thymic progenitors (ETPs). Previous work has shown that ETPs possess T and natural killer lymphoid potentials, and rare subsets of ETPs also possess B lymphoid potential, suggesting an origin from lymphoid-restricted progenitor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
364
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(404 citation statements)
references
References 30 publications
29
364
10
1
Order By: Relevance
“…It was initially thought that thymic settling progenitors lost myeloid potential before acquiring either T or B potential but a few recent studies showed that some progenitors within the thymus had lost B potential while retaining myeloid potential [49][50][51]. These data raised some controversy as it was questioned as to whether this myeloid differentiation occurs under physiological conditions within the thymus itself [52,53] but it was very recently reported that ETPs give rise to the majority of thymic granulocytes [54].…”
Section: Hematopoietic Precursor Differentiation Within the Thymusmentioning
confidence: 99%
“…It was initially thought that thymic settling progenitors lost myeloid potential before acquiring either T or B potential but a few recent studies showed that some progenitors within the thymus had lost B potential while retaining myeloid potential [49][50][51]. These data raised some controversy as it was questioned as to whether this myeloid differentiation occurs under physiological conditions within the thymus itself [52,53] but it was very recently reported that ETPs give rise to the majority of thymic granulocytes [54].…”
Section: Hematopoietic Precursor Differentiation Within the Thymusmentioning
confidence: 99%
“…It is generally believed that the so-called thymic seeding precursor (TSP) still has the capability of generating B cells, NK cells, DCs and other myeloid cells [2,5,6,10,11]. Upon receiving the Notch signal, the differentiation potential towards the B-cell lineage of the TSP is rapidly lost [2,10,11], whereas other lineage options are still maintained [2,5,6,10,11]. However, a recent study using an IL-7Ra reporter mouse indicated that the non-T-cell lineage differentiation of these progenitors is not, or only very rarely, occurring under physiologic conditions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In transplantation settings, it has been shown that different progenitors can home to the thymus and generate T cells [1][2][3][4][5][6][7][8][9]. However, under physiological conditions the role of each of these progenitors is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest a community with T-ALL, 26,27,47 which could be related to the existence of the recently identified common macrophage-T progenitor. 48,49 Both MYST3-linked AMLs and T-ALLs could originate from this common progenitor; variation in the dosage of regulatory factors could further induce leukemia in either the T-lymphoid or myelomonocytic lineage. The regulation of early myelomonocytic differentiation, which is controled by a complex network of factors, 50 is affected at several levels in t(8;16) leukemia including the formation of chimeric HATs, amplification of MYB and overexpression of HOXA genes.…”
Section: Myb Hox and Myst3-linked Amlsmentioning
confidence: 99%